2022
DOI: 10.21203/rs.3.rs-1239555/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Auxora Vs. Placebo for the Treatment of Patients with Severe COVID-19 Pneumonia: A Randomized Clinical Trial

Abstract: Background: Calcium release-activated calcium (CRAC) channel inhibitors block proinflammatory cytokine release, preserve endothelial integrity and may effectively treat patients with severe COVID-19 pneumonia. Methods: CARDEA was a phase 2, randomized, double-blind, placebo-controlled trial evaluating the addition of Auxora, a CRAC channel inhibitor, to corticosteroids and standard of care in adults with severe COVID-19 pneumonia. The primary endpoint was time to recovery through Day 60, with secondary endpoi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…A correlation analysis of D-dimer, imputed P/F, and status on the ordinal scale at 168 hours showed that the decrease in Ddimer levels noted in the rst 72 hours after treatment with Auxora correlated with an increase in the imputed P/F over the same time period (r: -0.193, P<0.05) which in turn correlated with improvement on the ordinal scale at 168 hours (r: 0.218, P<0.01). As reported previously, the median time to recovery for patients in the e cacy group treated with Auxora was 7 days (168 hours) [14].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…A correlation analysis of D-dimer, imputed P/F, and status on the ordinal scale at 168 hours showed that the decrease in Ddimer levels noted in the rst 72 hours after treatment with Auxora correlated with an increase in the imputed P/F over the same time period (r: -0.193, P<0.05) which in turn correlated with improvement on the ordinal scale at 168 hours (r: 0.218, P<0.01). As reported previously, the median time to recovery for patients in the e cacy group treated with Auxora was 7 days (168 hours) [14].…”
Section: Resultssupporting
confidence: 75%
“…In addition, the potential mechanism of action of Auxora in decreasing D-dimer levels would be assessed by testing the endothelial biomarkers Angiopoietin-1, Angiopoietin-2, and renin, as well as the in ammatory biomarker soluble CD25 (sCD25). The improved clinical outcomes noted in CARDEA from the treatment of severe COVID-19 with Auxora, including reductions in mortality at Days 30 and 60, have been previously published [14]. We now report the results from the testing of samples for D-dimer and biomarker levels and analyzing the correlation of the changes to outcomes.…”
Section: Introductionmentioning
confidence: 78%
“…As reported previously, the median time to recovery for patients in the e cacy group treated with Auxora was 7 days (168 hours). 14 The ANCOVA model includes Baseline value of the endpoint as a covariate and treatment as xed effect.…”
Section: Resultsmentioning
confidence: 99%
“…The improved clinical outcomes noted in CARDEA from the treatment of severe COVID-19 with Auxora, including reductions in mortality at Days 30 and 60, have been previously published. 14 We now report the results from the testing of samples for D-dimer and biomarker levels and analyzing the correlation of the changes to outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…7F). In a complementary approach, the tool SOCE inhibitor SKF96365 and a recently identified inhibitor CM4620, which (as Auxora TM , CalciMedica) has progressed to phase 3 clinical trials in acute inflammatory disease conditions (40), impaired the SOCE in wildtype TNBC cells and further reduced the residual SOCE in EHD2-KO cells (Fig. 6C).…”
Section: Ehd2 Promotes Pro-metastatic Traits In Tnbc Cells By Upregul...mentioning
confidence: 99%